Are ads bothering you?

Ex 4.1

Ex 4.1, 1
Important
Deleted for CBSE Board 2022 Exams

Ex 4.1, 2 Deleted for CBSE Board 2022 Exams

Ex 4.1, 3 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 4 Deleted for CBSE Board 2022 Exams

Ex 4.1, 5 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 6 Deleted for CBSE Board 2022 Exams

Ex 4.1, 7 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 8 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 9 Deleted for CBSE Board 2022 Exams

Ex 4.1, 10 Deleted for CBSE Board 2022 Exams

Ex 4.1, 11 Important Deleted for CBSE Board 2022 Exams You are here

Ex 4.1, 12 Deleted for CBSE Board 2022 Exams

Ex 4.1, 13 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 14 Deleted for CBSE Board 2022 Exams

Ex 4.1, 15 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 16 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 17 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 18 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 19 Deleted for CBSE Board 2022 Exams

Ex 4.1, 20 Deleted for CBSE Board 2022 Exams

Ex 4.1, 21 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 22 Deleted for CBSE Board 2022 Exams

Ex 4.1, 23 Important Deleted for CBSE Board 2022 Exams

Ex 4.1, 24 Important Deleted for CBSE Board 2022 Exams

Last updated at May 29, 2018 by Teachoo

Ex 4.1,11 Prove the following by using the principle of mathematical induction for all n ∈ N: 11.2.3 + 12.3.4 + 13.4.5 + ……..+ 1𝑛 𝑛 + 1(𝑛 + 2) = 𝑛(𝑛 + 3)4(𝑛 + 1)(𝑛 + 2) Let P (n) : 11.2.3 + 12.3.4 + 13.4.5 + ……..+ 1𝑛 𝑛 + 1(𝑛 + 2) = 𝑛(𝑛 + 3)4(𝑛 + 1)(𝑛 + 2) For n = 1, L.H.S = 11.2.3 = 16 R.H.S = 1.(1 + 3)4(1 + 1)(1 + 2) = 1.44.2.3 = 12.3 = 16 Hence, L.H.S. = R.H.S , ∴ P(n) is true for n = 1 Assume P(k) is true 11.2.3 + 12.3.4 + 13.4.5 + ……..+ 1𝑘 𝑘 + 1(𝑘 + 2) = 𝑘(𝑘 + 3)4(𝑘 + 1)(𝑘 + 2) We will prove that P(k + 1) is true. R.H.S = 𝑘 + 1 𝑘 + 1+ 34 𝑘 + 1+ 1 𝑘 + 1+ 2 L.H.S = 11.2.3 + 12.3.4 + 13.4.5 + ……..+ 1 𝑘 + 1 𝑘 + 1+ 1( 𝑘 + 1+ 2) Rough Factorizing 𝐤𝟑+ 𝟒+ 𝟗𝐤+ 𝟔𝐤𝟐 Let f(k) = k3+ 4+ 9k+ 6k2 Putting k = − 1 f(−1) = (−1)3+ 4+9 −1+6 (−1)2 = −1 + 4− 9+6 = 0 Thus, (k + 1) is a factor of f(k) ∴ f(k) = (𝑘+1)( 𝑘2+5𝑘+4)